A.B.C.'s of behavioral forensics : applying psychology to financial fraud prevention and detection - Ramamoorti, Sridhar (New Jersey. John Wiley & sons, 2013)
Understand how the psychologies of fraudsters and their victims interact as well as what makes auditors/investigators/regulators let down their guard. Learn about the psychology of fraud victims, including boards of directors and senior management, and what makes them want to believe fraudsters, and therefore making them particularly vulnerable to deception.
Includes bibliographical references and index.
oif 15/06/15
Loan
Keywords: Fraud; Criminal psychology; Fraud - prevention